Pertumbuhan dan perkembangan ulat grayak jagung (Spodoptera frugiperda Smith) dengan pakan buatan berbahan dasar kedelai (Glycine max L.): Growth and development of fall armyworm (Spodoptera frugiperda Smith) with soybean-based artificial diet (Glycine max L.) - Istiqomah Desi, Isti; Kustiati, Kustiati; Hernowo, Kukuh (Perhimpunan Entomologi Indonesia, 2025)
The fall armyworm (Spodoptera frugiperda Smith) is an invasive pest of corn crops in Indonesia. The development of S. frugiperda rearing techniques based on artificial feed is important to support various research projects on this species. This study aims to study the growth and development of S. frugiperda using soybean-based artificial feed (Glycine max L.). The study utilized first-instar larvae of S. frugiperda adults obtained from the Rasau Jaya Village Corn Farm. A total of 800 larvae were used to obtain accurate and representative data on the insect’s development. The variables observed included several important aspects, such as the survival rate at each stage (from larva to adult), growth morphometry at the sixth instar larva and pupa stages to understand changes in body size and shape, the duration of each stage to determine the length of each developmental phase, and the sex ratio to determine the proportion of males and females in the population. The survival rate data of S. frugiperda imagoes obtained were then analyzed using Microsoft Excel 2013 and presented descriptively to provide a clear and detailed overview of the research results. The research results showed that the survival rate of S. frugiperda at each growth stage averaged above 75%. The lifespan of the larval stage was 12.80 ± 1.00 days, the pupal stage was 7.80 ± 0.77 days, and the female imago (9.55 ± 2.42 days), while the male (7.39 ± 1.77 days). The sex ratio of males to females is 1:1.02. These results indicate the excellent potential of soybean-based artificial feed as the primary diet for maintaining S. frugiperda in the laboratory.